Biomechanical properties of expanded sheep skin / Nur Ain Sabrina Manssor - Nur Ain Sabrina, Manssor (2014)
Tissue expansion provides extra tissue which is useful for surgical reconstruction field and had been utilized since ages ago. Tissue expansion using self-inflating tissue expander had made its breakthrough in recent years. However similar issue arises whether the quality of tissue produced is comparable with original tissue. Therefore, the objectives of this study were to investigate the surface topography and elastic properties of expanded skin tissue at the macro and ultrastructural levels. Two groups of five adult male Dorper sheep were used in the study. One group acted as the control group and the other was implanted subcutaneously with cylindrical 20 x 5 mm osmotic tissue expanders at the lower limb region, and allowed to reach equilibrium, and harvested. The surface roughness and elastic modulus analysis were carried out using the Alicona 3D Optical Analyzer and BioAFM. The force spectroscopy test was performed on collagen fibrils at 10 points. In a separate set of experiments, samples from both groups were subjected to uniaxial tensile test and the elastic moduli at initial region (E0) and linear terminal region (E∞) as well as the limit strain were obtained. The average surface roughness (0.55 ± 0.27 μm) was significantly (p<0.05) lower in the expanded group (1.42 ± 0.64 μm). It was observed that the collagen fibrils in the expanded tissues were thinner. The modulus of the collagen fibrils in the expanded skin was 45.9 ± 24 MPa whereas the modulus of collagen fibrils in normal skin was 36.1 ± 29.5 MPa with no significant difference (p >0.05). As for the tensiometric parameters tested on bulk skin tissue, the E0 are 0.27 ± 0.19 MPa and 0.85 ± 0.67 MPa for normal and expanded skin, respectively. The E∞ obtained for normal and expanded groups are 2.14 ± 1.46 MPa and 4.4 ± 1.97 MPa, respectively. The limit strain for expanded skin is lower (0.3 ± 0.2)compared to normal skin (0.50 ± 0.16). The surface topography of the expanded skin shows evidence of fibers being stretched; therefore it affects the resting tension of the collagen fibrils, thus producing slightly higher elastic modulus of expanded skin and fibrils. However, from these experiments it was not possible to prove a possibility of new tissue generation in expanded skin because it requires concurrent histological experiments.